Is there a need for pneumococcal vaccination programs for the homeless to prevent invasive pneumococcal disease?. (2nd September 2021) - Tyrrell, Gregory; Lee, Cerina; Eurich, Dean
ABSTRACT: Introduction: Homeless are a vulnerable segment of society at risk for infections. Invasive pneumococcal disease (IPD) infections are increasingly identified in homeless as a major contributor of morbidity and mortality. Very few countries have recommended pneumococcal vaccination programs for the homeless. Areas covered: A literature review of IPD in the homeless from 1980 to 2020 in PubMed and Scopus using terms, 'homeless, ' and 'homelessness, ' and after 'chronic' or 'transitory' homeless was conducted. Gray literature from the CDC, WHO and major governmental agencies/organizations were included. Terms for IPD eligible for inclusion in the database search included 'pneumococcal disease, ' 'invasive pneumococcal disease, ' ' Streptococcus pneumoniae .' This included outbreaks of pneumococcal disease in the homeless, clinical characteristics associated with pneumococcal disease in the homeless, pneumococcal vaccines and vaccination recommendations for the homeless. Expert opinion: Homeless populations are at increased risk for IPD in comparison to the general population. This is due to clinical conditions experienced by the homeless including alcoholism and cigarette smoking. In addition, a collection of specific pneumococcal serotypes are associated with IPD in this group. Pneumococcal vaccine programs aimed at this population would likely decrease the incidence of IPD for this group and contribute to better overall health for the homeless.